Fuels or microclimate? Understanding the drivers of fire feedbacks at savanna-forest boundaries - HOFFMANN, WILLIAM A.; JACONIS, SUSAN Y.; MCKINLEY, KRISTEN L.; GEIGER, ERIKA L.; GOTSCH, SYBIL G.; FRANCO, AUGUSTO C. (Austral ecology, 2012)
The higher flammability of tropical savanna, compared with forest, plays a critical role in mediating vegetation‐environment feedbacks, alternate stable states, and ultimately, the distribution of these two biomes. Multiple factors contribute to this difference in flammability, including microclimate, fuel amount and fuel type. To understand this transition in flammability, we studied fuel characteristics and microclimate across eight savanna–forest boundaries in south‐central Brazil. At each boundary, the environment was monitored for one week with automated measurements of near‐surface wind speed, air temperature, relative humidity and presence of dew. Manual measurements were performed to quantify fuel amounts and fuel moisture. These data were used to parameterize the fire behaviour model BehavePlus5 in order to simulate fire behaviour over the savanna–forest boundary. There were strong gradients across the boundary in all variables with the exception of total fuel load. During the day, savannas had higher wind speed and air temperature, and lower relative humidity and fuel moisture than forests. Although fuel loads were similar in savanna and forest, savanna was characterized by lower fuel bulk density, largely because of the presence of grasses. Based on these measurements, the fire behaviour model predicted savanna fires to be faster, more intense, and with greater flame lengths, relative to forest. A sensitivity analysis indicated that the primary cause of these differences was the low fuel bulk density characteristic of grassy fuels, with lesser contributions from wind speed, fuel moisture and total fuel load. These results indicate that the dominance of grassy fuels is the primary cause of the high flammability of savanna.